Analisis Perencanaan Pajak Dalam Pemilihan Pemajakan UMKM Antara Peraturan Pemerintah Nomor 23 Tahun 2018 Dibandingkan Pasal 31E Undang-Undang Pajak Penghasilan Terhadap Efisiensi Pembayaran Pajak Penghasilan Badan Pada PT. KOP Mandiri Sejahtera Tahun 2020 - Abriyaldi Abriyaldi; Chairil Anwar Pohan (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Taxation is the main source of state revenue because it accounts for about 78% of state revenue (realization in 2020). One of the government's policies to increase revenue is to provide incentives for MSME businesses through Government Regulation Number 23 of 2018. This regulation applies to MSMEs that have a gross turnover of up to Rp. 4,800,000,000 per year. This study aims to determine the comparison of corporate income tax payments of PT. Kop Mandiri Sejahtera in 2020 using Government Regulation Number 23 of 2018 compared to Article 31E of the Income Tax Law. The analysis is carried out related to tax planning carried out by the company in the context of tax payment efficiency. This study used descriptive qualitative method. The data collection of this research was done by using interview, documentation and observation techniques. The results showed that the policies taken by PT. Kop Mandiri Sejahtera, namely using Government Regulation Number 23 of 2018 in calculating the company's corporate income tax obligations in 2020 resulting in higher income tax payments compared to the use of Article 31E of the PPh Law.